THE ANALYSIS OF GUAVA SUPPLY CHAIN; CASE STUDY AT KAMPUNG JAMBU CIMAUNG WEST JAVA INDONESIA - Silitonga, Elisabet; Azis, Anton (ANALISIS, 2022)
Kampung Jambu Cimaung is a place for cultivating horticultural commodities, who sold their crops both local and export needs. This study aims to determine the actors, flows, as well as driving and inhibiting factors of the guava supply chain in Kampung Jambu. The method used is a qualitative descriptive method and data collection techniques are carried out using interviews and simple observations. The research uses data reduction and data presentation for concluding. The results showed that the supply chain activity of guava in Kampung Jambu Cimaung is quite good, there are five links in the supply chain activities of Kampung Jambu, the supply-chain pattern of Kampung Jambu includes modern patterns, the flow of information, information on selling prices in the international market from exporters is not conveyed To Kampung Jambu, the main driving factors for production activities are high consumer demand and globalization, while the biggest inhibiting factors for supply chains are climate and lack of manpower. Kampung Jambu is expected to create collaboration for every supply chain actor, especially suppliers and consumers, and implement effective and efficient supply chain management.